الضّغوط النفسية وعلاقتها بالرضا عن الحياة لدى أساتذة التعليم المتوسط بالجزائر - مختار بن عبد السلام (Universty Of El-oued جامعة الوادي, 2024)
الملخص: تهدف الدراسة إلى معرفة علاقة الضغوط النفسية على الرضا عن الحياة لدى أساتذة التعليم المتوسط بالجزائر من خلال عينة من أساتذة ولايات الجنوب الكبير الجزائري، كما هدفت إلى معرفة أثر كل من الجنس والأقدمية على الضغوط النفسية والرضا عن الحياة. وللتحقق من فرضيات الدراسة، استخدم الباحث المنهج الوصفي التحليلي، واستخدم عينة طبقية عشوائية من مجتمع الدراسة والتي تكونت من 308 أستاذاً وأستاذة. وقد استعمل الباحث مقياس الضغوط النفسية لعسكر وآخرون (1986)، ومقياس الرضا عن الحياة لمحمد الدسوقي (1998). وبعد تطبيق المقياسين تم تحليل البيانات باستخدام برنامج التحليل الإحصائي SPSS. وقد توصلت الدراسة إلى النتائج التالية: -مستوى الضغوط النفسية لدى أساتذة التعليم المتوسط بالجزائر من خلال عينة بولايات الجنوب الكبير الجزائري كان متوسطاً، بمعدل = (79.58) وبوزن نسبي العام (56.84)، -مستوى الرضا عن الحياة لدى أساتذة التعليم المتوسط بالجزائر من خلال عينة بولايات الجنوب الكبير الجزائري كان مرتفعاً، بمعدل= (109.15) بوزن نسبي (75.25). -دلّ معامل الارتباط (R) على أن هناك علاقة ارتباطية موجبة بين الضغوط النفسية والرضا عن الحياة لدى أساتذة التعليم المتوسط بالجزائر من خلال عينة بولايات الجنوب الكبير الجزائري. -دلّ معامل الارتباط (R2) على قوة المتغير المستقل الضغوط النفسية في التنبؤ بالرضا عن الحياة لدى أساتذة التعليم المتوسط من خلال عينة بولايات الجنوب الكبير الجزائري. -لا توجد فروق ذات دلالة إحصائية في متوسطات درجات الضغوط النفسية لدى عينة من أساتذة التعليم المتوسط بالجزائر من خلال عينة بولايات الجنوب الكبير الجزائري تعزى لمتغيري الجنس والأقدمية في المهنة والتفاعل بينهما. توجد فروق ذات دلالة إحصائية في متوسطات درجات الرضا عن الحياة لدى أساتذة التعليم المتوسط بالجزائر من خلال عينة بولايات الجنوب الكبير الجزائري تعزى لمتغير الجنس، ولا توجد فروق ذات دلالة إحصائية تعزى لمتغير الأقدمية في المهنة، ولا توجد فروق ذات دلالة إحصائية تعزى للتفاعل بين الجنس والأقدمية في المهنة. واستنادًا إلى النتائج المتوصّل إليها قدمت الدّراسة مجموعة من الاقتراحات التي تخدم الموضوع، وتحدد آفاقه ومساهماته العلمية. Résumé : فرنسية أو انجلزية The study aims to know the effect of psychological stress on life satis-faction among teachers of middle education in Algeria through a sample of teachers from the states of the great south of Algeria., It also aimed to know the impact of both race and seniority on psychological stress and life satis-faction. To verify the hypotheses of the study, the researcher used the analytical descriptive approach, using a random cast sample of the study community consisting of 308professors. The researcher used the psychomotor for Askar and others (1986)and life satisfaction measure: for Mohamed El-Desouky (1998). After applying the two measures, the data were analyzed using the sta-tistical analysis program SPSS. The study's findings were as follows: -The results of the statistical analysis showed that the level of psycho-logical pressures of middle education teachers in the states of the Algerian Great South was medium, at a rate = (79.58)and general relativity(56.84), -The results also showed that the level of satisfaction with life among middle education teachers in the states of the Algerian Great South was high, at a rate=(109.15)onwards(75.25), -The correlation coefficient (R) indicated that there is a positive correla-tion between psychological stress and life satisfaction among teachers of in-termediate education in Algeria, through a sample of the states of the great south of Algeria. -The correlation coefficient (R2) indicated the strength of the independ-ent variable, psychological stress, in predicting life satisfaction among teach-ers of intermediate education in Algeria, through a sample of the states of the great south of Algeria. -There are no statistically significant differences in the average degrees of psychological stress among a sample of teachers of intermediate educa-tion in Algeria through a sample of the states of the great south of Algeria due to the variables of gender and seniority in the profession and the interac-tion between them. -There are statistically significant differences in the average degrees of satisfaction with life among teachers of intermediate education in Algeria through a sample of the states of the great south of Algeria due to the gender variable, and there are no statistically significant differences due to the vari-able of seniority in the profession, and there are no statistically significant differences due to the interaction between gender and seniority in the profes-sion. Based on the results reached, a set of proposals were developed that serve the subject of the study, and define its horizons and scientific contribu-tions.
"دراسة ميدانية بولايات الجنوب الكبير الجزائري"
أطروحة دكتوراه تخصص علم النفس المدرسي في العُلوم الاجتِماعيَّة والإنسَانيَّة
Keywords: الضّغوط النفسية -الرضا عن الحياة -أساتذة التعليم المتوسط; Psychological stress-life satisfaction-professors of Intermediate Education.